2023
DOI: 10.3389/fenvs.2023.1267413
|View full text |Cite
|
Sign up to set email alerts
|

The characteristic and potential of green trade between China and regional comprehensive economic partnership countries

Yujie Xu,
Xianchun Liao,
Meicun Li

Abstract: This paper analyze the characteristics of green trade between China and Regional Comprehensive Economic Partnership (RCEP) countries from 2001 to 2020, and then adopts a stochastic frontier gravity (SFG) model and trade inefficiency (TIE) model to analyze the trade potential and the influencing factors of green trade between China and RCEP countries. The main conclusions are as follows: the green trade value continues to grow, with Japan and South Korea as the main green trade partners. The competitive advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Li et al (2023)evaluated the level of green trade in China's provinces using the SYS-GMM method to examine the impact of green trade on China's pollution emissions.Can Muhlis (2022)used the "Green Trade Openness Index" to measure the importance of green products in a region and proved that the presence of green products in a country's trade basket can reduce its ecological footprint. Xu et al (2023)used the stochastic frontier gravity model (SFG) and the trade inefficiency model (TIE) to analyze the potential and influencing factors of green trade between China and the countries of the Regional Comprehensive Economic Partnership (RCEP). The literature analysis found that the current research on green trade mainly focuses on the utility of green trade and the effect of exogenous variables, such as environmental policies, on green trade.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2023)evaluated the level of green trade in China's provinces using the SYS-GMM method to examine the impact of green trade on China's pollution emissions.Can Muhlis (2022)used the "Green Trade Openness Index" to measure the importance of green products in a region and proved that the presence of green products in a country's trade basket can reduce its ecological footprint. Xu et al (2023)used the stochastic frontier gravity model (SFG) and the trade inefficiency model (TIE) to analyze the potential and influencing factors of green trade between China and the countries of the Regional Comprehensive Economic Partnership (RCEP). The literature analysis found that the current research on green trade mainly focuses on the utility of green trade and the effect of exogenous variables, such as environmental policies, on green trade.…”
Section: Introductionmentioning
confidence: 99%